Who goes where in couples and pairs? Effects of sex and handedness on side preferences in human dyads. Issue 4 (4th July 2022) - Rodway, Paul; Schepman, Astrid
ABSTRACT: There is increasing evidence that inter-individual interaction among conspecifics can cause population-level lateralization. Male–female and mother–infant dyads of several non-human species show lateralised position preferences, but such preferences have rarely been examined in humans. We observed 430 male–female human pairs and found a significant bias for males to walk on the right side of the pair. A survey measured side preferences in 93 left-handed and 92 right-handed women, and 96 left-handed and 99 right-handed men. When walking, and when sitting on a bench, males showed a significant side preference determined by their handedness, with left-handed men preferring to be on their partner's left side and right-handed men preferring to be on their partner's right side. Women did not show significant side preferences. When men are with their partner they show a preference for the side that facilitates the use of their dominant hand. We discuss possible reasons for the side preference, including males prefering to occupy the optimal "fight ready" side, and the influence of sex and handedness on the strength and direction of emotion lateralization.